2015
DOI: 10.1371/journal.pntd.0003935
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phylogenetic Studies on Schistosoma japonicum and Its Snail Intermediate Host Oncomelania hupensis: Origins, Dispersal and Coevolution

Abstract: Background Schistosoma japonicum causes major public health problems in China and the Philippines; this parasite, which is transmitted by freshwater snails of the species Oncomelania hupensis, causes the disease intestinal schistosomiasis in humans and cattle. Researchers working on Schistosoma in Africa have described the relationship between the parasites and their snail intermediate hosts as coevolved or even as an evolutionary arms race. In the present study this hypothesis of coevolution is evaluated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 62 publications
(64 reference statements)
1
24
0
Order By: Relevance
“…With the elevation of the Qinghai-Tibet Plateau, the change in climate [32], the change in ecological environment, and the development of geographical isolation, the snail species gradually differentiated in this location, producing O. h. robertsoni . In addition, we found that the divergence time of S. japonicum was approximately 3.8 Ma [33, 34], close to the divergence time of O. h. robertsoni , which may represent the beginning of the parasitic relationship between S. japonicum and O. hupensis [35]. When S. japonicum began to live in the snail body and whether there was a symbiotic relationship between the species remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…With the elevation of the Qinghai-Tibet Plateau, the change in climate [32], the change in ecological environment, and the development of geographical isolation, the snail species gradually differentiated in this location, producing O. h. robertsoni . In addition, we found that the divergence time of S. japonicum was approximately 3.8 Ma [33, 34], close to the divergence time of O. h. robertsoni , which may represent the beginning of the parasitic relationship between S. japonicum and O. hupensis [35]. When S. japonicum began to live in the snail body and whether there was a symbiotic relationship between the species remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, migrating uninfected individuals may be more susceptible to parasite infection having not been exposed to Schistosoma spp. in their pre-migration environment [55]. …”
Section: Discussionmentioning
confidence: 99%
“…At the same time, passive snail dispersal may also be mediated by human and animal movement, and these were not captured in our study. Construction of roads and railways such as the Greater Mekon Subregion (GMS) Chengdu-Kunming corridor and the GMS North-South Corridor through mountainous terrain will breach geographical barriers in the study region, potentially opening up new ranges into which snails may expand [55, 66]. …”
Section: Discussionmentioning
confidence: 99%
“…Because soils with dense vegetation, such as grassland, woodland and forest, inherently have low drainage and high water retentive capacities, they tend to support smaller water bodies and water courses which are the preferred habitat of the Lymnaeidae [2, 4, 11]. Compared with grassland, forest and woodland have been shown to confer a lower risk of fascioliasis infestation because of the lower level of solar radiation in these habitat types.…”
Section: Discussionmentioning
confidence: 99%